2020
DOI: 10.1167/iovs.61.12.3
|View full text |Cite|
|
Sign up to set email alerts
|

Long Noncoding RNA OIP5-AS1 Promotes Cell Apoptosis and Cataract Formation by Blocking POLG Expression Under Oxidative Stress

Abstract: Purpose Cataract, a clouding of the intraocular lens, is the leading cause of blindness. The lens-expressed long noncoding RNA OIP5-AS1 was upregulated in lens epithelial cells from patients with cataracts, suggesting its pathogenic role in cataracts. We investigated the regulatory role of OIP5-AS1 in the development of cataracts as well as potential RNA binding proteins, downstream target genes, and upstream transcription factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…OIP5‐AS1 has been implicated in the development of cataracts, where under oxidative stress, it is activated by TFAP2A and upregulated in B3 cells and lens epithelial cells 73 . Knockdown of OIP5‐AS1 resulted in a reduction of B3 cell apoptosis due to H 2 O 2 ‐induced oxidative stress, as well as an absence of lens opacity under oxidative stress, all of which contribute to the development of cataracts 73 .…”
Section: A Single Lncrna: a Myriad Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…OIP5‐AS1 has been implicated in the development of cataracts, where under oxidative stress, it is activated by TFAP2A and upregulated in B3 cells and lens epithelial cells 73 . Knockdown of OIP5‐AS1 resulted in a reduction of B3 cell apoptosis due to H 2 O 2 ‐induced oxidative stress, as well as an absence of lens opacity under oxidative stress, all of which contribute to the development of cataracts 73 .…”
Section: A Single Lncrna: a Myriad Diseasesmentioning
confidence: 99%
“…OIP5‐AS1 has been implicated in the development of cataracts, where under oxidative stress, it is activated by TFAP2A and upregulated in B3 cells and lens epithelial cells 73 . Knockdown of OIP5‐AS1 resulted in a reduction of B3 cell apoptosis due to H 2 O 2 ‐induced oxidative stress, as well as an absence of lens opacity under oxidative stress, all of which contribute to the development of cataracts 73 . The hypothesis is that OIP5‐AS1 contributes to regulation of the HuR‐mediated mitochondrial apoptosis pathway in B3 cells by mediating the destruction of POLG mRNA in the presence of oxidative stress, which could support the eventual development of cataracts 73 …”
Section: A Single Lncrna: a Myriad Diseasesmentioning
confidence: 99%
“…Cyrano a lncRNA namely OIP5-AS1 works in vivo as an up-regulating system, with the capacity of renewal embryonic stem cells, modulating miR7 MicroRNAs (miRNAs, miR), capable of regulating post-transcriptional gene expressions; disproportion in the miRNA network has been associated with the development of many pathological conditions and diseases, including not only cataracts but cancer [86][87][88][89].…”
Section: Oxidative Stress As a Key Element In Cataract Formationmentioning
confidence: 99%
“…Studies have found that although long non-coding RNAs (LncRNAs) cannot directly encode proteins, they can regulate the expression of apoptosis-related genes before, during, and after gene transcription, thereby interfering with apoptosis [11][12][13][14]. To determine which LncRNAs are related to the hypoxic apoptosis of BMSCs, we used LncRNA chip combined with bioinformatics analysis.…”
Section: Introductionmentioning
confidence: 99%